First lactation production performance of Mehsana buffaloes under Field Progeny testing Programme in Semi-arid region of Gujarat - PRAJAPATI, BHAVESH M; GUPTA, Jay PRAKASH; CHAUDHARI, JAGDISH D; PARMAR, GIRISH A; PANCHASARA, HARSHAD H; Chauhan, Hareshbhai D; Ankuya, Kanubhai J; PRAJAPATI, M N (Indian Journal of Dairy Science, 2018)
The present investigation was carried out using data of first lactation production records of 7825 Mehsana buffaloes sired by 200 bulls spread over a period of 25 years (1989-2013), collected from the Dudhsagar Research and Development Association (DURDA), Dudhsagar Dairy, Mehsana to obtain the genetic and non-genetic parameters of first lactation total milk yield (FLTMY), first lactation length (FLL), first wet average (FWA) and average test day fat yield (ATDFY). The effects of non-genetic factors were assessed by fixed linear model. Heritability and phenotypic/genetic correlations were estimated by paternal half sib correlation method. Period of calving, season of calving and age group was significant for all the traits. Cluster had significant effect on all the traits except FLL. The heritability for FLTMY, FWA and ATDFY was high in magnitude and thus indicates sufficient additive genetic variance for affecting the selection to improve the traits genetically. The first lactation total milk yield had positive phenotypic and genetic correlation with FLL, FWA and ATDFY.